2012
DOI: 10.1371/journal.pone.0043353
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of HERG Channel Activity by β-catenin

Abstract: The multifunctional protein ß-catenin governs as transcription factor the expression of a wide variety of genes relevant for cell proliferation and cell survival. In addition, ß-catenin is localized at the cell membrane and may influence the function of channels. The present study explored the possibility that ß-catenin participates in the regulation of the HERG K+ channel. To this end, HERG was expressed in Xenopus oocytes with or without ß-catenin and the voltage-gated current determined utilizing the dual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It is known that the main function of Apc is to degrade cytosolic levels of b-catenin, whose dysregulation is considered a major cause of tumor development. As previous studies from Carlos Munoz's laboratory showed that b-catenin increased the hERG1 protein levels within the oocyte cell membrane [42], the increased hERG1 channel activity detected in the polyps of Apc min/+ mice could be attributed to the overexpression of b-catenin, widely described in this animal model [43]. It is worth noting that, at difference from what happens in the small intestine, the loss of function of Apc is not sufficient per se to trigger the development of tumors in the colon, where adjunctive genetic events are required for the transition from microadenomas to macroscopic tumors to be accomplished [44].…”
Section: Discussionmentioning
confidence: 73%
“…It is known that the main function of Apc is to degrade cytosolic levels of b-catenin, whose dysregulation is considered a major cause of tumor development. As previous studies from Carlos Munoz's laboratory showed that b-catenin increased the hERG1 protein levels within the oocyte cell membrane [42], the increased hERG1 channel activity detected in the polyps of Apc min/+ mice could be attributed to the overexpression of b-catenin, widely described in this animal model [43]. It is worth noting that, at difference from what happens in the small intestine, the loss of function of Apc is not sufficient per se to trigger the development of tumors in the colon, where adjunctive genetic events are required for the transition from microadenomas to macroscopic tumors to be accomplished [44].…”
Section: Discussionmentioning
confidence: 73%
“…In support of this, β-catenin is found to co-localize with insulin granules at cell junctions in MIN6 pseudoislets [58]. Another explanation would be a regulation of ion fluxes, since there is a significant body of evidence that β-catenin can regulate the location and/or function of ion transporters at the plasma membrane in β-cells [59][60][61][62][63]. The resulting changes in ion currents could affect insulin granule release.…”
Section: Discussionmentioning
confidence: 90%